Pelatihan Strategi Pemasaran Digital Pada UMKM di Dusun Tembere Desa Batu Nampar - Muhamad Zaril Gapari; Muhammad Hanafi; Syamsur Rizal (Indonesia, 2024)
Marketing strategy training for Micro, Small, and Medium Enterprises (UMKM) in Tembere Hamlet, Batu Nampar Village, aims to improve the understanding and ability of UMKM actors in marketing products effectively and efficiently. This training is designed to provide insight into the importance of digital marketing, the use of social media, and community-based marketing strategies to expand market reach and increase the competitiveness of local products. Through interactive counseling methods and direct practice, participants are expected to be able to identify market potential, design appropriate marketing strategies, and optimize existing resources. The expected results of this training are increased participants' knowledge and skills in designing marketing strategies that can accelerate the growth and sustainability of their businesses. This training is expected to have a positive impact on improving the local economy in Tembere Hamlet, by strengthening the presence of UMKM in a wider market.